Omecamtiv Mecarbil Abolishes Length-Mediated Increase in Guinea Pig Cardiac Myofiber Ca(2+) Sensitivity - Gollapudi, Sampath K. (Biophys J, 2017)
Omecamtiv mecarbil (OM) is a pharmacological agent that augments cardiac contractile function by enhancing myofilament Ca(2+) sensitivity. Given that interventions that increase myofilament Ca(2+) sensitivity have the potential to alter length-dependent activation (LDA) of cardiac myofilaments, we tested the influence of OM on this fundamental property of the heart. This is significant not only because LDA is prominent in cardiac muscle but also because it contributes to the Frank-Starling law, a mechanism by which the heart increases stroke volume in response to an increase in venous return. We measured steady-state and dynamic contractile indices in detergent-skinned guinea pig (Cavia porcellus) cardiac muscle fibers in the absence and presence of 0.3 and 3.0 μM OM at two different sarcomere lengths (SLs), short SL (1.9 μm) and long SL (2.3 μm). Myofilament Ca(2+) sensitivity, as measured by pCa(50) (−log of [Ca(2+)](free) concentration required for half-maximal activation), increased significantly at both short and long SLs in OM-treated fibers when compared to untreated fibers; however, the magnitude of increase in pCa(50) was twofold greater at short SL than at long SL. A consequence of this greater increase in pCa(50) at short SL was that pCa(50) did not increase any further at long SL, suggesting that OM abolished the SL dependency of pCa(50). Furthermore, the SL dependency of rate constants of cross-bridge distortion dynamics (c) and force redevelopment (k(tr)) was abolished in 0.3-μM-OM-treated fibers. The negative impact of OM on the SL dependency of pCa(50), c, and k(tr) was also observed in 3.0-μM-OM-treated fibers, indicating that cooperative mechanisms linked to LDA were altered by the OM-mediated effects on cardiac myofilaments.